Epilepsy care pathway: The Finnish model - Reetta Kälviäinen; Zakarya Hadj‐Allal; Jarkko Kirjavainen; Reina Roivainen; Tarja Linnankivi; Jukka Peltola; Kai Eriksson; Salla Lamusuo; Tuire Lähdesmäki; Johanna Annunen; Päivi Vieira; Virpi Tarkiainen; et al. (Epilepsia Open)
Abstract Objective Integrated care pathways are essential for consistent, effective epilepsy care, offering equal access and quality regardless of socioeconomic status. They must align with the WHO Global Action Plan on Epilepsy, ensuring best practices and cost‐effective management. We describe the Finnish national epilepsy care pathway, which includes multiple levels of care, from initial diagnosis to long‐term care for all types of epilepsy, with a specific focus on rare and complex cases integrated with the European Reference Network (ERN) for Rare and Complex Epilepsies EpiCARE. Methods In 2017, the Finnish government nominated Kuopio University Hospital to coordinate diagnostics and care for severe epilepsy in Finland. A national multidisciplinary consensus panel, including specialists from both adult and pediatric neurology departments across all five Finnish university hospitals and from the patient organization, was established. The resulting pathway was adopted into the current Finnish evidence‐based current care guidelines for epilepsy. Results The Finnish epilepsy care pathway focuses on timely referrals, continuity of care and enhanced communication between healthcare providers at different levels of care. Patient involvement is assured with an individualized digital application offering secure online messaging, a seizure calendar, and remote visits. The pathway enhances virtual consultations and includes regular national diagnostic multidisciplinary meetings for severe epilepsies before selected cases are consulted in ERN EpiCARE meetings. Significance This Finnish model for epilepsy care provides a streamlined, multidisciplinary approach to diagnosis and treatment and combines modern digital tools, data sharing, and peer support. This pathway can serve to model how integrated healthcare systems can effectively manage complex conditions. Plain Language Summary We describe the Finnish national epilepsy care pathway, which includes multiple levels of care, from initial diagnosis to long‐term care for all types of epilepsy, with a specific focus on rare and complex cases integrated with the European Reference Network (ERN) for Rare and Complex Epilepsies EpiCARE. Finnish model for epilepsy care provides a streamlined, multidisciplinary approach to diagnosis and long‐term treatment of epilepsy. The pathway enhances virtual consultations and includes national and European‐level diagnostic multidisciplinary meetings for severe epilepsies. To improve outcomes, we emphasize the use of modern digital tools, data sharing, and peer support.